Latest development of approved COVID-19 drugs and COVID-19 drugs undergoing late stage clinical trials - Feng, Bingru; Fu, Kai (Frontiers in Drug Discovery, 2023)
As the world adapts to living with SARS-CoV-2, the continuous emergence of new variants has become a primary focus of current studies. In this review, we examined a range of available COVID-19 drugs, including FDA-regulated drugs and those undergoing late-stage clinical trials. Some FDA-regulated drugs, such as Veklury (remdesivir), Olumiant (baricitinib), and Actemra (tocilizumab), have garnered primary clinical status in treatment guidelines, supported by sufficient clinical evidence. Conversely, EUA-authorized therapies, such as some antiviral agents, have demonstrated lower efficacy due to the virus’s constant mutation. We also focused on COVID-19 drugs undergoing late-stage clinical trials, some of which have raised controversy in their administration, such as colchicine and corticosteroids, while others are worth exploring regarding their timing. Several ongoing multi-drug clinical trials are of particular interest, including the “MEDIC-LAUMC” trial that explores drug co-administration, and “ACTIV-2” and “ACTIV-3” trials that compare the effects of different drugs for non-hospitalized and hospitalized patients, respectively. These ongoing clinical trials at a late stage provide essential clinical evidence for future drug authorization and have the potential to provide better drug administration strategies for COVID-19 variants. We look forward to the continued exploration of drug co-administration, comprehensive clinical evidence for treatment, and the investigation of different potential drug utilization.